Some questions of the judiciary (Journal of actual problems of jurisprudence, 2018)
The article deals with the problems of the judiciary in the Republic of Kazakhstan. The authors give the analysis of the concepts «judicial power», «power» and «government», as indicated by the inherent characteristics of the judiciary. At the same time the author of a comparative analysis of the legislation on the courts and the status of judges, the analysis of the various views expressed about the term «judicial authority». Identify problem points the place and role of the judiciary in the system of separation of powers on a branch in the Republic of Kazakhstan. The judiciary is characterized as autonomous, independent and subject only to the law of one of the branches of power on a branch.Key words: the judiciary, the government powers, the courts, the status of judges, the courts system.